Validation of self-reported diabetes in a representative sample of São Paulo city - Mariane de Mello Fontanelli; Juliana Araújo Teixeira; Cristiane Hermes Sales; Michelle Alessandra de Castro; Chester Luiz Galvão Cesar; Maria Cecilia Goi Porto Alves; Moisés Goldbaum; Dirce Maria Marchioni; Regina Mara Fisberg
ABSTRACT OBJECTIVE To validate the self-reported diabetes mellitus in adults and older adults living in the city of São Paulo, Brazil. METHODS We have used data of 569 subjects (284 adults and 285 older adults), participants of the population-based cross-sectional study Inquérito de Saúde do Município de São Paulo (Health Survey of São Paulo). Fasting glucose ≥ 7.0 mmol/L (126 mg/dL) and/or use of drugs (oral hypoglycemic and/or insulin) defined the diagnosis of diabetes mellitus. We have validated the self-reported diabetes mellitus by calculating the sensitivity, specificity, positive predictive values, and negative predictive values. We have used Poisson regression with robust variance to verify the factors associated with the sensitivity of the self-reported datum. For all analyses, we have considered the sample design of the study. RESULTS The sensitivity of self-reported diabetes mellitus was 63.8% (95%CI 49.2-76.3), specificity was 99.7% (95%CI 99.1-99.9), positive predictive value was 95.5% (95%CI 84.4-98.8), and negative predictive value was 96.9% (95%CI 94.9-98.2). The correct reporting of diabetes mellitus was more prevalent among older adults (PR = 2.0; 95%CI 1.2-3.5) than among adults. CONCLUSIONS The use of the datum of self-reported diabetes mellitus is valid, especially among older adults living in the city of São Paulo. The results highlight the need to track diabetes mellitus in asymptomatic subjects who have one or more risk factors for it, mainly in the adult population of this city.